Nordlyd III : Norrbotten NEO at KLANG – Copenhagen Avantgarde Music Festival, 5th of June 2018 at Koncertkirken Copenhagen. (2018)
Norrbotten NEO and Conductor Petter Sundkvist performs the third part of the NORDLYD project - The sound of the Nordic languages, with focus on our mother tongue. The project consists of three newly ordered pieces with the language as a focus. The three composers who have written music, which will include their own voices are Ylva Lund Bergner, Bergrún Snæbjörgdóttir and Bente Leiknes Thorsen from Sweden, Iceland and Norway. In addition, there is also a piece from Denmark, Bent Sørensen's trio Schattenlinie from 2010, and Per Mårtensson's Nemea's Secret, inspired by the story of the lion outside the city of Nemea in Greek mythology. The sixth piece of the programme is a world premiere of the Finnish Lauri Supponen's Gaz aux étages. Validerad;2018;Nivå 2;2018-12-20 (svasva)